2015
DOI: 10.1002/ejp.743
|View full text |Cite
|
Sign up to set email alerts
|

Personality subtypes and chest pain in patients with nonobstructive coronary artery disease from the TweeSteden Mild Stenosis study: mediating effect of anxiety and depression

Abstract: Type D personality, but not negative affectivity or social inhibition, was related to chest pain in nonobstructive CAD, which was mediated by negative mood states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…In total, 883 patients were eligible for participation and received information on the study, as has previously been described in more detail. 16 In total, 547 (62%) patients signed informed consent, of which 523 completed a set of questionnaires which were send and returned by postal mail. The research protocol was approved by the medical ethics committee of the Elisabeth Hospital Tilburg, and written informed consent was obtained from all participants (METC Brabant protocol number: NL22258.008.08).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 883 patients were eligible for participation and received information on the study, as has previously been described in more detail. 16 In total, 547 (62%) patients signed informed consent, of which 523 completed a set of questionnaires which were send and returned by postal mail. The research protocol was approved by the medical ethics committee of the Elisabeth Hospital Tilburg, and written informed consent was obtained from all participants (METC Brabant protocol number: NL22258.008.08).…”
Section: Methodsmentioning
confidence: 99%
“…Type D personality has been associated with poor physical and mental health status 14 , 15 and more chest pain in patients with NOCAD. 16 …”
mentioning
confidence: 99%
“…For example, veterans with stable CAD and a new diagnosis of depression at follow-up reported more angina, physical limitation and lower treatment satisfaction [24]. Amore recent study in patients with non-obstructive CAD identified an association between type D personality – characterized by negative affective states – and increased frequency of chest pain [13]. We have previously reported that depression in women after myocardial infarction was associated worse angina and physical limitation in addition to worse outcomes [25].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the association between depression and chest pain is dependent on the presence or severity of CAD, or whether this comorbidity is due to other factors, remains unclear. Both pain and depression share common neurochemical pathways [12], and a few studies have suggested that patients with non-obstructive CAD and depression have greater incidence of persistent chest pain [7,13]. Understanding the relation between depression and chest pain is important in order to provide the impetus to study whether treatment of depression improves chest pain, and whether individuals presenting with chest pain should be screened for depression.…”
Section: Introductionmentioning
confidence: 99%
“…6164 The TweeSteden Mild Stenosis (TWIST) observational study, as an example, demonstrated an association between type D personality and persistent chest pain. 65 …”
Section: The Psychiatric Differential Diagnosismentioning
confidence: 99%